Three-dimensional assisted techniques vs. conventional fixation in complex periarticular fractures: a systematic review of outcomes and complications - Gong, Jinpeng; Sun, Yanjun; Ma, Yupeng; Han, Dong; Ge, Junbo (Frontiers in Bioengineering and Biotechnology, 2025)
Complex periarticular fractures are difficult to manage as anatomical reduction and stable fixation using conventional methods are challenging. Patient-specific three-dimensional (3D) printed implants and surgical guides have been developed with recent technical advances in 3D printing technology. This study systematically evaluates 3D printing–assisted methods, including patient-specific implants surgical guides, and preoperative bone models, against traditional fixation techniques for periarticular fractures by examining intraoperative duration, fracture reduction quality, radiographic results, and functional outcomes and complication rates. The research team carried out a literature search on PubMed, Scopus, and Web of Science for clinical comparative studies published during the period of 2015–2025. The selected research evaluated the effectiveness of patient-specific 3D-printed implants and surgical guides as well as preoperative planning tools. Risk of bias (ROB) was assessed with ROBINS-I. Primary outcomes were collected and described. Seven studies (randomized controlled trials and cohort studies) fulfilled the inclusion criteria. Operative time and blood loss were significantly shorter in most of the studies using 3D-assisted techniques. Fracture reduction accuracy was improved in several studies with smaller articular step-off and higher rate of anatomical reduction. Functional outcome was similar in most of the studies with modest improvement reported in a few. Reduction in complications was seen or a similar rate in the 3D group. One study found no significant benefit of 3D guidance over conventional treatment. 3D-assisted fixation shows promise in enhancing surgical precision and efficiency in complex periarticular fractures. While early results are favorable, further high-quality research is needed to validate its long-term clinical benefits and cost-effectiveness.